DIAMAGNETISM IN THE CYLINDRICAL QUANTUM DOT WITH PARABOLIC CONFINEMENT POTENTIAL - Ghaltaghchyan, H.Ts.; Kazaryan, E.M.; Sarkisyan, H.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
Diamagnetic properties of the electron gas in a cylindrical quantum dot with parabolic confinement potential have been investigated. The analytical expressions have been obtained for mean energy, mean magnetization and mean magnetic susceptibility of the electron gas. The diamagnetic character of such system has been shown.